2004
DOI: 10.1002/nau.20026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high frequency deep brain stimulation on urine storage and voiding function in conscious minipigs

Abstract: Transurethral cystometry was a feasible examination technique in pigs. The findings demonstrate that high frequency deep brain stimulation changes the bladder characteristics in the storage phase. Since bladder pressure and capacity responded differently to interruption of stimulation distinct neural mechanisms must be involved in the modulation of sensory information on bladder tension and stretch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…4,6 Medical antiparkinsonian treatment may influence bladder control, but in an unpredictable manner. 7,8 Studies in animal models 9 and in humans 10,11 suggest beneficial effects on storage of urine by stimulation in the STN. The aim of this study was to evaluate LUTS and bladder control in patients with Parkinson's disease, in a prospective manner before and after implantation of electrodes in the STN.…”
mentioning
confidence: 97%
“…4,6 Medical antiparkinsonian treatment may influence bladder control, but in an unpredictable manner. 7,8 Studies in animal models 9 and in humans 10,11 suggest beneficial effects on storage of urine by stimulation in the STN. The aim of this study was to evaluate LUTS and bladder control in patients with Parkinson's disease, in a prospective manner before and after implantation of electrodes in the STN.…”
mentioning
confidence: 97%
“…The Göttingen minipig has gained increased interest during the last decade as a non-primate large experimental animal, also including its use as an animal model in PD (Mikkelsen et al 1999;Danielsen et al 2000;Sørensen et al 2000;Watanabe et al 2001;Dall et al 2002;Bjarkam et al 2004Bjarkam et al , 2005Bjarkam et al , 2008aDalmose et al 2004Dalmose et al , 2005Lind et al 2007;Lindvall and Wahlberg 2008;Jensen et al 2009;Rosendal et al 2009). For further refinement and use of the animal model in PD research, detailed knowledge of the SNc is crucial.…”
Section: Discussionmentioning
confidence: 98%
“…Its gyrated brain is large (6 9 5 9 4 cm) compared with rodents, with a great subcortical anatomical resemblance to primates (Felix et al 1999;Larsen et al 2004;Bjarkam et al 2008b;Rosendal et al 2009). The large brain enables PET and MRI scanning procedures as well as conventional neurosurgery, stereotaxic neurosurgery and surgical implantation of devices intended for human use Sørensen et al 2000;Watanabe et al 2001;Dall et al 2002;Bjarkam et al 2004Bjarkam et al , 2005Bjarkam et al , 2008aDalmose et al 2004;Lindvall and Wahlberg 2008;Jensen et al 2009;Rosendal et al 2009). The pig genome resembles that of primates (Lind et al 2007); the pig is affordable compared with primates, and many of the ethical considerations combined with using primates as experimental animals may be avoided (Goodman and Check 2002), making it possible to include more animals in studies, and thereby hopefully obtain more valid results.…”
Section: Introductionmentioning
confidence: 97%
“…Recent reports have suggested that the basal ganglia modulate the micturition reflex in both experimental animals 13 and humans, 14 since lesions in the basal ganglia can cause severe urinary urge incontinence. Several previous studies have examined the role of the basal ganglia on the micturition reflex by electrical stimulation of the globus pallidus and subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%